Vision driven lane changing system of self driving car - Meshkat, Mashook Mohammad; Mustafa, Shehab; Deen, Tahmid Al; Das, Mrinmoy (Brac University, 2024)
This final year design project is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Electrical and Electronic Engineering, 2023.